2005
DOI: 10.4102/ojvr.v72i1.227
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of chicken anaemia virus infection in Nigerian indigenous chickens : research communication

Abstract: <span style="font-family: arial,helvetica;">Serum samples from 20 out of 180 (11.1 %) apparently healthy Nigerian indigenous chickens were negative for antibodies against chicken anaemia virus using the enzyme-linked immunosorbent assay (ELISA). Of the 160 positive sera (88.9 %), 12 (7.5 %) had titres ranging from 1 500-3 000, 46 (28.8 %) had titres from 3 000-5 000 while 102 (63.8 %) had titres between 5 000-11 000. The overall mean titre value was 5 845 <span style="text-decoration: underline;">+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Because vaccination against CIAV is not practiced in the country, the presence of antibodies in serum samples indicates field infections. Apart from earlier reports on CIAV prevalence from many parts of the world, similar to our findings, recently, several researchers from African and Asian countries have observed high seroprevalence rates in their poultry flocks (Emikpe et al., 2005; Roussan, 2006; Farhoodi et al., 2007; Oluwayelu, 2010) indicating CIAV to be an emerging pathogen worldwide. The inadequate responses to vaccinations, flaring up of other infectious diseases, and secondary infections, commonly observed in field conditions, might be associated with CIAV infection.…”
Section: Discussionsupporting
confidence: 91%
“…Because vaccination against CIAV is not practiced in the country, the presence of antibodies in serum samples indicates field infections. Apart from earlier reports on CIAV prevalence from many parts of the world, similar to our findings, recently, several researchers from African and Asian countries have observed high seroprevalence rates in their poultry flocks (Emikpe et al., 2005; Roussan, 2006; Farhoodi et al., 2007; Oluwayelu, 2010) indicating CIAV to be an emerging pathogen worldwide. The inadequate responses to vaccinations, flaring up of other infectious diseases, and secondary infections, commonly observed in field conditions, might be associated with CIAV infection.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, A. auricula polysaccharide is found to have many biological activities, this compound possesses antioxidant activity, anticoagulant activity, decreases blood sugar, and can improve well-being [9][10][11][12]. People are paying increasing attention to its exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Backyard chickens (Gallus gallus domesticus), which constitute about 80 % of the estimated 150 million chicken population in Nigeria, have been implicated in the epidemiology of some viral diseases of poultry in the country (Abdu 1988;Ohore, Ozegbe, Emik pe & Okojie 2002) and concerns have been express ed about their ability to harbour CAV. Recent serologic studies on commercial and backyard chick ens in Nigeria revealed a high prevalence of CAV in fection (Owoade, Oluwayelu, Fagbohun, Ammer laan, Mulders & Muller 2004;Emikpe, Oluwayelu, Ohore, Oladele & Oladokun 2005;Oluwayelu 2006). While Ducatez, Owoade, Abiola & Muller (2006) reported sequence diversity of Nigerian commercial chicken CAVs, they did not investigate backyard chicken flocks.…”
Section: Introductionmentioning
confidence: 99%